Effect of yield criteria on the formability prediction of dual-phase steel sheets. (November 2017) - Cheng, C.; Wan, M.; Wu, X.D.; Cai, Z.Y.; Zhao, R.; Meng, B.
Highlights: Equivalent stress-strain data from Yld2000-2d-Var represent the hardening behavior. FLCs are accurately predicted by M-K model with Yld2000-2d-Var and Swift law. The stretch formability depends on the suitable material model and FLCs. The precise yield criterion is of great significance to the formability prediction. Abstract: The yield criterion is the basis of the material model that can describe the plastic behavior of the material under any possible stress states. The influence of diverse yield criteria on the formability prediction was explored via analyzing the hardening behavior and the forming limit of DP590 and DP780 sheets in this paper. The potential of the yield criterion to describe the hardening behavior of sheet metal was evaluated by comparing the equivalent stress-strain curves from the cruciform biaxial tensile tests with the uniaxial stress-strain curve. To characterize the hardening behaviors of dual-phase steel sheets under large strain condition, the hydraulic bulge tests were employed to obtain the equivalent stress-strain data based on different yield criteria. Accordingly, the material models including diverse yield criteria and hardening laws were used to calculate the theoretical forming limit curves (FLCs) based on the M-K model. Through comparing the predicted FLCs and the experimental ones from Nakazima tests, it was found that the theoretical FLCs based on the M-K model largely depend on the accurate yield criterion and hardening law. In addition, the numerical simulations of two stretch tests were carried out to verify the validity of the material models and the theoretical FLCs. The results indicated that the accurate yield criterion is of great significance to the description of hardening behavior and the prediction of FLCs. Graphical abstract: